Sputum derived biomarkers of anti-tuberculosis drug activity in early bactericidal activity (EBA) studies - Kayigire, Xavier A. (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.